Intranasal nanophotosensitizer enables safe and broad-spectrum photodynamic inactivation of respiratory viruses - Han, Sunmi; Seitkazina, Assel; Heo, Jeongyun; Kim, Se-young; Kim, Sujin; Jeon, Sung-Ho; Park, Yung Hun; Lim, Taehun; Kim, Bohyeon; Rajoriya, Shivani; Luu, Quy Son; Lee, Youngbok; et al. (Elsevier BV, 2025)
The emergence of highly transmissible respiratory viruses, including SARS-CoV-2 and its variants, emphasizes the urgent need for safe, variant-agnostic, and self-administered antiviral strategies. Here, we present a nanotheranostic platform (MBSD) based on methylene blue nanoparticles stabilized with a primary fatty acid naturally found in human nasal mucosa, designed for intranasal photodynamic inactivation (PDI). This nanoformulation enhances cellular permeability and singlet oxygen generation at sites of viral infection through strategic ion pairing and micellization using clinically approved excipients. MBSD demonstrated superior uptake and intracellular singlet oxygen generation in human nasal epithelial cells compared to free methylene blue. Upon exposure to red light, PDI treatment with MBSD significantly reduced viral gene expression and infectivity across multiple RNA and DNA viruses-including influenza A, SARS-CoV-2 variants (B.1 and Delta), Zika, Vaccinia, and emerging paramyxoviruses-with sub-nanomolar to low-nanomolar EC50 values. In murine models, a single intranasal MBSD-mediated PDI treatment attenuated disease progression, markedly reduced lung viral burden and inflammation, and improved survival outcomes. In addition, repeated PDI treatments showed no detectable toxicity to normal mucosal tissues, indicating a favorable safety profile. These findings highlight MBSD-mediated PDI as a clinically translatable, non-invasive nanomedicine strategy that offers broad-spectrum antiviral efficacy and mucosal safety, supporting its potential as a frontline theranostic intervention for earlystage management of respiratory virus outbreaks.